2016
DOI: 10.1016/j.addbeh.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet use, well-being, self-esteem and self-control: Data from a high-school survey in China

Abstract: Given the prevalence of Internet use among youth, there is concern that a subset of Internet-using youth may exhibit problematic or addictive patterns of Internet use. The present study examines the association between problematic Internet use (PIU), demographic variables, and health-related measures among Chinese adolescents. Survey data from 1552 adolescents (male = 653, mean age = 15.43 years) from Jilin Province, China, were collected. According to the Young Diagnostic Questionnaire for Internet Addiction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
109
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(133 citation statements)
references
References 63 publications
11
109
1
12
Order By: Relevance
“…Therefore, the greater the use of the Internet, the lesser the psychological well-being, and vice versa. It has been observed that when the use of the Internet becomes excessive and problematic, there are more tensions, deterioration of psychosocial well-being and alteration of mood regulation, which has an impact on their psychological well-being (Lai et al, 2015;Mei et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the greater the use of the Internet, the lesser the psychological well-being, and vice versa. It has been observed that when the use of the Internet becomes excessive and problematic, there are more tensions, deterioration of psychosocial well-being and alteration of mood regulation, which has an impact on their psychological well-being (Lai et al, 2015;Mei et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to research focused on specific psychopathologies, other studies have investigated the connection between the use of the Internet and psychological well-being (Çardak, 2013;Casale, Lecchi & Fioravanti 2015;Lai et al, 2015;Mei, Yau, Chai, Guo & Potenza, 2016). Some authors have observed that abusive use of Internet and online interactions entails individuals" spending time on Internet at the expense of other daily activities, which leads to a consequent isolation, academic impairment, and problems in family relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Mei et al, 2016;Shek and Yu, 2016;Wang et al, 2011). The frequency of connection to the Internet and the amount of hours spent online were observed to increase the risk of PIU with a dose response effect, a common finding in cross-sectional adjusted studies(Johansson and Götestam, 2004;Koyuncu et al, 2014;Ni et al, 2009;Sasmaz et al, 2014;Wang et al, 2011).…”
mentioning
confidence: 90%
“…In the adjusted generalized linear mixed models without mediation, a positive relationship between depressive symptoms and PIU, opioid misuse, and sedative misuse was found, respectively. First, PIU may increase the risk of depressive symptoms due to adolescents with PIU showing poorer well-being, self-control, and self-esteem, which were reported to be positively associated with psychiatric disorders (including depressive symptoms) [34,35]. Similarly, Park et al reported that PIU was positively associated with depressive symptoms in Korean adolescents [10]; Dalbudak et al demonstrated that Internet addiction might increase vulnerability to depressive symptoms in students of Turkey [36]; and Tan et al found that PIU was significantly related to an increased risk of depressive symptoms among adolescents in Shantou, China [11].…”
Section: Discussionmentioning
confidence: 99%